Find the diff equation of family of circles with center on the line y= -x and passing through the origin.

THANK YOU :)

$(x - h)^2 + (y - k)^2 = r^2$

$(x - h)^2 + (y + h)^2 = 2h^2$

$2(x - h) + 2(y + h)y' = 0$

$(x - h) + (y + h)y' = 0$

$-h(1 - y') = -(x + yy')$

$h = \dfrac{x + yy'}{1 - y'}$

$\left( x - \dfrac{x + yy'}{1 - y'} \right)^2 + \left( y + \dfrac{x + yy'}{1 - y'} \right)^2 = 2\left( \dfrac{x + yy'}{1 - y'} \right)^2$

$\left[ \dfrac{(x - xy') - (x + yy')}{1 - y'} \right]^2 + \left[ \dfrac{(y - yy') + (x + yy')}{1 - y'} \right]^2 = 2\left( \dfrac{x + yy'}{1 - y'} \right)^2$

$\left[ (x - xy') - (x + yy') \right]^2 + \left[ (y - yy') + (x + yy') \right]^2 = 2\left( x + yy' \right)^2$

$(x + y)^2 (y')^2 + (x + y)^2 = 2(x + yy')^2$

Like us on Facebook

$(x - h)^2 + (y - k)^2 = r^2$

$(x - h)^2 + (y + h)^2 = 2h^2$

$2(x - h) + 2(y + h)y' = 0$

$(x - h) + (y + h)y' = 0$

$-h(1 - y') = -(x + yy')$

$h = \dfrac{x + yy'}{1 - y'}$

$\left( x - \dfrac{x + yy'}{1 - y'} \right)^2 + \left( y + \dfrac{x + yy'}{1 - y'} \right)^2 = 2\left( \dfrac{x + yy'}{1 - y'} \right)^2$

$\left[ \dfrac{(x - xy') - (x + yy')}{1 - y'} \right]^2 + \left[ \dfrac{(y - yy') + (x + yy')}{1 - y'} \right]^2 = 2\left( \dfrac{x + yy'}{1 - y'} \right)^2$

$\left[ (x - xy') - (x + yy') \right]^2 + \left[ (y - yy') + (x + yy') \right]^2 = 2\left( x + yy' \right)^2$

$(x + y)^2 (y')^2 + (x + y)^2 = 2(x + yy')^2$